Bacterial Contamination in Processed Chicken Shawarma (Meat) Sold in Various Parts of Lahore, Pakistan - Ahmad, Farooq; Abbas, Saqlain; Butt, Zahid Ali; Ali, Adnan Skhawat; Mahmood, Rashid; Ahmad, Maqsood; Farhan, Muhammad; Wahid, Abdul; Nawaz, Muhammad; Iftikhar, Aqsa (Pakistan Journal of Nutrition, 2013)
In this study bacterial flora of meat in chicken Shawarma (meat) were investigated from five different regions of Lahore. Samples were taken from internal and external part of Shwarma. The contamination was present in both external and internal part of meat. But external part was found to be little more contaminated as compared to internal part. Analysis of microbes includes E. coli, Salmonella, Aerobes and Coliforms. Microbs were found in order of Aerobes > E. coli > Salmonella there is not too much variation of contamination in different regions but there is variation among the number of bacteria. In every part Aerobes were in greater number as compared to E. coli and Salmonella. Shawarma analyzed from the Site III was more contaminated as compared to other sites. The external part of the product showed more microbial load as compared to internal part.